Making and Sharing the Space: Initiatives for Story-sharing and Reconciliation among Women and Men in South Africa and Northern Ireland - Ericson, M (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
In this article I present findings from my earlier research on reconciliation in South Africa and Northern Ireland, together with some issues raised by my current research project on “reconciliation in South Africa from women’s perspectives”. Reconciliation is seen as a process whereby the diverse “moral landscapes” held in a war-torn society are addressed, with the aim of building, rebuilding or transforming relationships between those in conflict. A common strategy is to provide “safe spaces” where people from all “sides” can broaden their “moral landscapes” and find sources of common ground by listening to, and being challenged by, each other’s life stories and personal experiences of the conflict. On the basis of my case studies, I identify some important conditions for such “story-sharing”, as well as certain dilemmas. I also ask critical questions about what beliefs and practices that may silence certain stories, and how space and power are shared between women and men in church and society, in particular in post-TRC South Africa.